ANALISIS POLA REKRUTMEN CALON LEGISLATIF PEREMPUAN DALAM PEMILIHAN UMUM TAHUN 2014 (Studi Kasus Komparasi Pola Rekrutmen Antara Dewan Pimpinan Daerah Partai Demokrasi Indonesia Perjuangan dan Partai Demokrat di Provinsi Jambi) - Luth (MIP UMY, 2016)
Recruitment pattern is a pattern, a model, a system or way of working that is used by political parties in the process of recruiting candidates. PDI-P and the Democratic Party is a great party in Indonesia and in the province of Jambi, In legislative elections in 2014 in the province of Jambi Democrats succeeded as the winner of the election by gaining nine seats four of whom were women, while the PDI-P as the winner at position 3 with 7 seats but no women candidates were elected. Therefore, the pattern of recruitment and the factors that influence the recruitment pattern of women candidates are in use DPD PDIP and the Democratic Party became the focus of study in this research. This study uses a qualitative method. The data collected with melaluhi depth interviews and documentation. As the informants in this study is the chairman, the board and the candidate of the PDI-P and the Democratic Party of Jambi Province. The results of this study indicate the recruitment pattern of female candidates PDI-P and the Democratic Party in legislative elections in 2014 in the province of Jambi together using the pattern of partisanship, meritocratic and compartmentalization. But the more dominant PDIP recruit female candidates of the pattern of partisanship by the number 8, while Democrats are more dominant meritocratic use patterns with the number of 10 people. Factors that influence the recruitment pattern of female candidates in the recruitment process PDIP is internal party level and request group deciding party policy. While the Democratic Party is only influenced by candidates who declare themselves to participate in the elections. Its conclusions and recommendations of this study is the recruitment pattern that is in use DPD PDIP and the Democratic Party is composed of a pattern of partisanship, meritocratic and Compatamization.Faktor the factors that influence the recruitment process includes, Demand policymakers and candidate states themselves. Subsequent research in order to focus on methods mixmethod citing data obtained much more complete to compare patterns of recruitment of women candidates are in use by a political party.